Association between AST/ALT ratio and the risk of gestational diabetes mellitus in Korean pregnant women - Dongqian Yang; Yuqin Shen; Rong Shuai (PLoS ONE, 2025)
Background The aspartate aminotransferase to alanine aminotransferase (AST/ALT) ratio is associated with insulin resistance (IR) and diabetes mellitus, but its association with gestational diabetes mellitus (GDM) has been less well-studied. Objective Our study aimed to investigate whether the AST/ALT ratio is associated with GDM in a population of pregnant Korean women. Methods The study was a secondary analysis of a prospective cohort study. It included 623 pregnant women who were at 10–14 weeks of gestation between November 2014 and September 2016. We downloaded and analyzed the data in October 2024. A total of 575 singleton pregnant women were included after excluding missing variables. All participants were followed up until the birth of their children. AST/ALT ratio was obtained by dividing AST by ALT. AST/ALT ratio was used as a continuous variable, and a quartile categorical variable was used for analysis. Logistic regression models were used to estimate the relationship between AST/ALT ratio and GDM. Subgroup and sensitivity analyses were conducted to explore the stability of this relationship. Restricted cubic spline (RCS) curve fitting was employed to investigate potential non-linear associations. Results Pregnant women were stratified into quartiles based on their AST/ALT ratios, with the following cutoff values: Q1 (<1.167), Q2 (1.167–1.499), Q3 (1.5–1.818), and Q4 (>1.818). The overall mean AST/ALT ratio across all participants was 1.6 ± 1.0. After adjusting for confounders, the AST/ALT ratio was negatively associated with GDM (OR=0.45, 95% CI: 0.2–0.99), with results confirmed by sensitivity and subgroup analyses. Conclusion This study demonstrated that a lower AST/ALT ratio in early pregnancy was independently and negatively associated with the risk of GDM. The AST/ALT ratio may serve as a potential early biomarker to identify pregnant women at higher risk of GDM, contributing to targeted preventive strategies.